A ineficácia dos princípios orientadores das nações unidas sobre empresas e direitos humanos como mecanismo de proteção nas violações cometidas por transnacionais - Moraes, Fabiano Lopes de (2017)
This scientific research aims at drawing a parallel between the UN Guiding Principles for Business and Human Rights and their effectiveness as mechanisms for protecting Human Rights in violations committed by companies. For this, the work begins to verify the classic theory of Alberto Asquini about companies, locking a parallel with contemporary companies and the need for protection of human rights, their social and sustainable responsibility for the economic tripod. After that, a descriptive study will be carried out on the UN human rights protection mechanisms, and the access mechanisms and regulatory procedures to repair cases where there is a violation. Finally, the UN Guiding Principles for Business and Human Rights will be explored further and the central question will be raised as to whether it is effective as a mechanism for the protection of human rights and whether there is a need to create an international treaty as a means of linking States And Companies in the protection and reparation in cases of violation of Human Rights. For this research was used the hypothetical inductive method and bibliographical survey aims to demonstrate the current state and possible mechanisms for protection of human rights in violations by companies.